Psychiatric Presentation of Anti-NMDA Receptor Encephalitis - Endres, Dominique; Rauer, Sebastian; Kern, Winfried; Venhoff, Nils; Maier, Simon J.; Runge, Kimon; Süß, Patrick; Feige, Bernd; Nickel, Kathrin; Heidt, Timo; Domschke, Katharina; Egger, Karl; et al. (Frontiers in Neurology, 2019)
Background: Anti-N-methyl D-aspartate (NMDA) receptor encephalitis is an autoimmune condition characterized by neuropsychiatric symptoms, including epileptic seizures, movement disorders, autonomic instability, disturbances of consciousness, paranoia, delusions, and catatonia. Ovarian teratomas and viral infections, typically Herpes simplex viruses, have previously been demonstrated to precipitate anti-NMDA receptor encephalitis, but in many cases, the trigger remains unclear. The detection of anti-NMDA receptor antibodies in cerebrospinal fluid (CSF), in combination with other CSF, electroencephalography (EEG), or magnetic resonance imaging (MRI) abnormalities, typically leads to diagnostic clarification. Case presentation: We present the case of a 22-year-old female patient who developed an acute polymorphic psychotic episode three days after receiving a booster vaccination against tetanus, diphtheria, pertussis, and polio (Tdap-IPV). Her psychiatric symptoms were initially diagnosed as a primary psychiatric disorder. Her MRI, EEG, and CSF results were non-specific. Anti-NMDA receptor IgG antibodies against the GluN1 subunit were detected in her serum (with a maximum titer of 1:320), but not in her CSF. [18F]fluorodeoxyglucose positron emission tomography (FDG-PET) showed pronounced relative hypermetabolism of her association cortices and a relative hypometabolism of the primary cortices, on the basis of which an anti-NMDA receptor encephalitis diagnosis was made, and treatment with a steroid pulse was initiated. The treatment led to fast and convincing clinical improvement with normalization of neuropsychological findings, considerable improvement of FDG-PET findings, and decreasing antibody titers. Conclusion: The patient’s psychiatric symptoms were most likely caused by anti-NMDA receptor encephalitis. Her polymorphic psychotic symptoms first occurred after she had received a Tdap-IPV booster vaccination. Although the vaccination cannot have caused the initial antibody formation since IgG serum antibodies were detected only three days after administration of the vaccine, the vaccine may have exerted immunomodulatory effects. MRI, EEG, and CSF findings were non-specific; however, FDG-PET identified brain involvement consistent with anti-NMDA receptor encephalitis. This case shows the importance of implementing a multimodal diagnostic work-up in similar situations. The negative CSF antibody finding furthermore fits to the hypothesis that the brain may act as an immunoprecipitator for anti-NMDA receptor antibodies.